Implementation of the Extreme Programming Method in the Reseller Module in Developing the Mitra.id Business Collaboration Platform for MSMEs - Al maura, Salsabil Syifa; Ambarsari, Nia; Al anshary, Faishal Mufied (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
The growth of Micro, Small and Medium Enterprises (MSMEs) plays an important role in driving the national economy, most business entities are classified as small and medium. In the digital era, the competitiveness of MSMEs can be increased through digitalization, such as the use of websites and social media. One effective solution is a reseller system, allowing individuals to start a business with minimal capital. This research aims to develop a reseller module in the Mitra.id application, a collaboration platform for MSME and reseller businesses. This application was developed with the PHP programming language, using the Laravel framework and the Extreme Programming method. The main features developed include authentication and authorization, profile management, product ordering, payment, real-time communication via chat, as well as a membership feature for access to exclusive price offer chat forums. The development process is tested using User Acceptance Testing (UAT). Test results show that the Mitra.id application meets user needs and objectives, with all features successfully completed. This indicates that the features developed in the first and second iterations have functioned well and met user expectations.Keywords: MSMEs; Resellers; Extreme Programming; User Acceptance Testing.Â AbstrakPertumbuhan Usaha Mikro, Kecil, dan Menengah (UMKM) berperan penting dalam mendorong ekonomi nasional, sebagian besar entitas usaha tergolong kecil dan menengah. Di era digital, daya saing UMKM dapat ditingkatkan melalui digitalisasi, seperti pemanfaatan website dan media sosial. Salah satu solusi yang efektif adalah sistem reseller, memungkinkan individu memulai usaha dengan modal minimal. Penelitian ini bertujuan mengembangkan modul reseller pada aplikasi Mitra.id, sebuah platform kolaborasi bisnis UMKM dan reseller. Aplikasi ini dikembangkan dengan bahasa pemrograman PHP, menggunakan framework Laravel dan metode Extreme Programming. Fitur utama yang dikembangkan meliputi autentikasi dan otorisasi, pengelolaan profil, pemesanan produk, pembayaran, komunikasi real-time melalui chat, serta fitur membership untuk akses ke forum chat penawaran harga yang eksklusif. Proses pengembangan diuji menggunakan User Acceptance Testing (UAT). Hasil pengujian menunjukkan bahwa aplikasi Mitra.id memenuhi kebutuhan dan tujuan pengguna, dengan semua fitur berhasil diselesaikan. Hal ini menandakan bahwa fitur-fitur yang dikembangkan pada iterasi pertama dan kedua telah berfungsi dengan baik dan memenuhi harapan pengguna.Â